Seat Theory in International Commercial Arbitration: Evolution from Lex Loci Arbitri to Lex Arbitri - Sarker, Maksuda (Dhaka University Law Journal, 2022)
Despite the continual effort of the business community to intercept international commercial arbitration from the precinct of national laws and courts, complete detachment is neither possible nor desirable. International arbitrations are affined to a national jurisdiction through the ‘seat theory’ which serves a profusion of inevitable objects including imparting legal basis to the Award. While serving its purposes, ‘seat theory’ converts lex loci arbitri of the seat into lex arbitri of the arbitration which results in the inescapable consequence of binding the parties with the mandatory provisions of lex loci arbitri. This conversion often encounters criticism for curtailing party autonomy, the main driving force behind opting for arbitration. This article scrutinizes the intricacies involved in such conversion with a special focus on the amplitude of party autonomy in drafting lex arbitri. After unrolling the relationship between lex loci arbitri and lex arbitri in ‘seat theory’, the article concludes that the problem inheres in the indifference of the parties in choosing the seat and the overzealous attitude of some States toward controlling international arbitration. It proposes internationalization of the outlook of different States toward international commercial arbitration to liberate ‘seat theory’ for the condemnation of the opponents. Dhaka University Law Journal, 2022, 33(1), 121-142